12
$\begingroup$

I'm trying to compute the following limit and would greatly appreciate your heartening feedback on my solution.

The limit:

$\lim_{\theta \to \frac{\pi}{2}} (\sec \theta - \tan \theta)$

My steps in deriving the solution:

Preliminary identities:

  1. $\sec \theta = \frac{1}{\cos \theta}$
  2. $\tan \theta = \frac{\sin \theta}{\cos \theta}$

$\frac{1}{\cos \theta}-\frac{\sin\theta}{\cos\theta} = \frac{1-\sin\theta}{\cos\theta} = \frac{1-\sin^2\theta}{(1+\sin\theta)\cos\theta} = \frac{\cos^2\theta}{\cos\theta}\cdot \frac{1}{1+\sin\theta} = \frac{\cos\theta}{1+\sin\theta} = \frac{0}{1+1}$

When $\theta \to \frac{\pi}{2}$ then $\cos(\frac{\pi}{2}) = 0$ and $\sin(\frac{\pi}{2}) = 1$

The answer being:

$\lim_{\theta \to \frac{\pi}{2}} (\sec \theta - \tan \theta) = 0$

$\endgroup$
2
  • 8
    $\begingroup$ It sounds good to me. Well done! $\endgroup$ – user0102 Feb 21 at 17:23
  • $\begingroup$ Welcome to Mathematics Stack Exchange. You should say $\lim...\color{red}=0$, not $\approx0$ $\endgroup$ – J. W. Tanner Feb 21 at 17:35
7
$\begingroup$

Your proof is fine. Here's another:$$\sec\theta,\,\tan\theta\to\infty\implies\sec\theta+\tan\theta\to\infty\implies\sec\theta-\tan\theta=\frac{1}{\sec\theta+\tan\theta}\to0.$$

$\endgroup$
3
  • $\begingroup$ I had an idea earlier that $\frac{1-\sin\theta}{\cos\theta} = 1-\tan\theta \to 0$, given that $\tan \theta \to 1$, or might this rationale be wrong? $\endgroup$ – Meilton Feb 21 at 19:27
  • $\begingroup$ @jj_ellison Notice in that idea you replaced $1/\cos\theta$ with $1$. While your equation is false, your two sides have the same limit provided $1/\cos\theta-1\to0$, which it would for $\theta\to0$ but not $\theta\to\pi/2$. In any case, $\sec\theta\to1$ only when $\tan\theta\to0\ne1$. $\endgroup$ – J.G. Feb 21 at 19:44
  • $\begingroup$ I have not seen your answer, I have put another and now I have seen that it is the same of your. +1 $\endgroup$ – Sebastiano Feb 21 at 21:12
2
$\begingroup$

Your approach is indeed the best way to tackle such problems, here is alternative way using L's hospital rule after applying the preliminary identities...

$\lim _{\theta\rightarrow 0}\frac{\left(1-\sin \theta \right)}{\cos \theta }=\lim _{\theta\rightarrow 0}\frac{\frac{d}{d \theta}\left(1-\sin \theta \right)}{\frac{d}{d \theta}\left(\cos \theta \right)}=\lim _{\theta\rightarrow 0}\frac{\left(-\cos \theta \right)}{\left(-\sin \theta \right)}=\lim _{\theta\rightarrow 0}\tan \theta =0$

Again, that was absolutely unnecessary, yet just in case it would be useful later...... :~)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.